PEMBENTUKAN BUDAYA SEKOLAH DI LINGKUNGAN SMKN 3 PALANGKA RAYA UNTUK MENINGKATKAN KUALITAS KINERJA GURU-GURU PRODUKTIF - APRILIA, PRISKA; SUHARDI, MUHAMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The role of teachers and schools is crucial in developing competent and competitive human resources. To produce graduates with high-quality human resources, teachers play a critical role in education and the learning process in schools. Currently, many schools and educational institutions are unaware of their school culture, resulting in no efforts for improvement or development of the school culture. Issues with school culture can lead to low student motivation and academic performance because the school does not become a conducive place for learning. This research aims to examine the school culture at SMKN 3 Palangka Raya and its role in the performance of productive teachers. This study is qualitative research in the form of a literature review related to: 1. School culture and its role in improving the performance of productive teachers; 2. the school culture at SMKN 3 Palangka Raya. School culture consists of habitual and ongoing activities that become the school’s identity. A positive school culture plays a role in enhancing the performance of productive teachers, which includes training on instrument creation and practical fieldwork. The school culture at SMKN 3 Palangka Raya, known as